The number and function of circulating CD34+CD133+ progenitor cells decreased in stable coronary artery disease but not in acute myocardial infarction. Issue 1 (11th July 2010) - Kondo, Takahisa; Shintani, Satoshi; Maeda, Kengo; Hayashi, Mutsuharu; Inden, Yasuya; Numaguchi, Yasushi; Sugiura, Kaichiro; Morita, Yasuhiro; Kitamura, Tomoya; Kamiya, Haruo; Sone, Takahito; Ohno, Miyoshi; et al.
Abstract : Objective: Circulating CD34 + CD133 + cells are one of the main sources of circulating endothelial progenitor cells (EPCs). Age is inversely related to the number and function of CD34 + CD133 + progenitor cells in stable coronary artery disease (CAD), but the relationship remains unclear in acute myocardial infarction (AMI). The authors aimed to clarify how ageing affects the number and function of mobilised CD34 + CD133 + progenitor cells in AMI. Design and results: Circulating CD34 + CD133 + progenitor cells were measured by flow cytometry. Measurements were made at admission for CAD, or on day 7 after the onset of AMI. In stable CAD (n=131), circulating CD34 + CD133 + cells decreased with age (r=−0.344, p<0.0001). In AMI, circulating CD34 + CD133 + cells did not correlate with age (n=50), and multivariate analysis revealed that the decreased number of circulating CD34 + CD133 + cells was associated with male sex and higher peak creatinine kinase. The ability to give rise to functional EPCs, which show good migratory and tube-forming capabilities, deteriorated among stable CAD subjects (n=10) compared with AMI subjects (N=6). Conclusions: In stable CAD, the number and function of circulating CD34 + CD133 + progenitor cells decreased with age, whereas those mobilised and circulating in AMI did not.